Agradecimiento: Carmen Granados, Jonathan Chaves, Javier Calvo, Ana Laura Murillo, Jeffry Ulate, Danny Arroyo, Adrián Arguedas y Ruddy Espinoza - Revista Electrónica Educare (Revista Electrónica Educare)
Documento adjunto